Leishmaniose visceral no Brasil - Marcondes, Mary [UNESP]; Rossi, Claudio Nazaretian (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Visceral leishmaniasis (VL) is among the most important vector-borne diseases that occur in Brazil, mainly due to its zoonotic nature. It is currently present in almost all Brazilian territory, and its control is a challenge both for veterinarians and for public health officials. The etiologic agent is Leishmania infantum (syn chagasi), and the main vector in Brazil is Lutzomyia longipalpis. Of all animals identified as reservoirs of VL, the dog is considered the most important domestic reservoir. Although the disease has already been identified in cats, the epidemiological role of this animal species is still unclear. This article presents a brief review of the epidemiological situation of the disease, its mode of transmission, clinical features in dogs and cats as well as possible risk factors associated with the occurrence of the disease in Brazil.

A leishmaniose visceral (LV) está entre as mais importantes doenças transmitidas por vetores que ocorrem no Brasil, principalmente devido ao seu caráter zoonótico. Atualmente, está presente em quase todo o território brasileiro, e seu controle é um desafio tanto para médicos veterinários como para agentes de saúde pública. O agente etiológico da doença é a Leishmania infantum (syn chagasi), e o principal vetor no Brasil é a Lutzomyia longipalpis. De todos os animais identificados como reservatórios da LV, o cão é considerado o reservatório doméstico mais importante. Apesar da doença já ter sido identificada em gatos, o papel epidemiológico desta espécie animal ainda é incerto. O presente artigo apresenta uma breve revisão sobre a situação epidemiológica da doença, a sua forma de transmissão, os aspectos clínicos nos cães e gatos, bem como possíveis fatores de risco associados à ocorrência da doença no Brasil.
Visceral leishmaniasis in Brazil
Keywords: Leishmania infantum; Leishmania chagasi; Dogs; Cats; Epidemiology; Leishmania infantum; Leishmania chagasi; Cães; Gatos; Epidemiologia